Impact of Pseudomonas spp. on Plant Growth, Lytic Enzymes and Secondary Metabolites Production - Waghunde, Rajesh R.; Sabalpara, Ambalal N. (Frontiers in Agronomy, 2021)
Seven strains of Pseudomonas spp. were isolated from the south Gujarat region of India. Antifungal and bacterial activities of bacterial strains were evaluated against important plant pathogens in vitro, among them PaRS found most effective. The indole acetic acid production was recorded in all isolated Pseudomonas spp. Seed treatment with PaRS at 6g/kg was significantly superior over the rest treatments for plant growth promotion (germination, shoot and root length, shoot and root weight, vigor index and shoot as well as root colonization) under standard roll towel method and pot condition. The maximum siderophore production was observed in PaRS and medium production in PfRB, PaNS and PfNC. PaNS and PaRS strains recorded strong HCN production but moderate production recorded in PaWP, PaWS and PfNC. The maximum phosphate solubalization zone (22mm) was found in PaRS. PaRS recorded maximum chitinase, ß-1,3-glucanase activity, hydrogen cynide and salicylic acid production as compare to other strains.